Functionalized Composite Coatings Based on Filled Powder Paint Processed in Planetary Ball Mill; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Panin S. V. Sergey Viktorovich (Materials Science in Mechanical Engineering, 2015)
Title screen